Relationship between the stiffness of the medial gastrocnemius and spatiotemporal variables during 100-m sprint running in collegiate sprinters - Norifumi Fujii; Katsuki Takahashi; Raki Kawama; Taku Wakahara (PLoS ONE, 2026)
Higher stiffness of the medial gastrocnemius (MG) has been reported to be associated with faster race time in 100-m sprint running. However, the association of muscle stiffness with spatiotemporal variables (i.e., step frequency, step length, flight time, stance time, flight distance, and stance distance), which are determinants of sprint running velocity, remains unknown. Thus, we aimed to elucidate the relationship between the passive/active stiffness of MG and spatiotemporal variables at the 50–60 m interval (maximal velocity phase) during 100-m sprint running. Using an ultrasound scanner (11 Hz), the shear wave velocity of MG in 21 male collegiate sprinters (100-m best race time: 11.03 ± 0.29 s) was measured at passive/active (during 20% and 50% of maximal voluntary isometric contraction [MVC] of plantar flexion) states as a proxy for muscle stiffness. Participants performed 100-m sprint runs, and their sprint running motion at the 50–60 m interval was recorded using a camera (240 Hz) to calculate spatiotemporal variables. The results showed that the shear wave velocity of MG at neither passive (0% MVC) nor active (20% and 50% MVC) states correlated with 100-m sprint time ( r = 0.189, 0.331, 0.102, p = 0.620, 0.429, and 0.659, respectively) or any spatiotemporal variables ( r = −0.264 to 0.422, p = 0.137 to 0.937). These results suggest the stiffness of MG might not be important for spatiotemporal variables of sprinters, at least with the performance level in this study.